Aspects of mistranslation from English into Ibibio: the case of Aids and the Ibibio Language Equivalent - Effiong Ekpenyong (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2008)
This paper examines the semantics of AIDS in Ibibio, one of Africa’s languages spoken in the Southern part of Nigeria. It asserts that “Udoño itiaita”, literally “Eight diseases”, which the Ibibio-speaking people adopted as AIDS equivalent in the language, is a mistranslation and semantically inaccurate. The findings show a phonological mix-up over AIDS and the number “eight” due to the accidental resemblance between them. The paper posits that when Ibibio native-speakers first heard about AIDS, they assumed it had to do with the number “eight”. This was the beginning of the problem, as AIDS and “eight” sound alike phonologically. An attempt is made to compare the Ibibio equivalent of AIDS with those of French, Hausa, Igbo and Yoruba. The result is that of Ibibio falling short semantically and failing the back-translation test. The paper avers that it is worrisome that “Udoño itiaita” is still retained as AIDS equivalent in Ibibio decades after it was wrongly adopted, making it to look as if the word was untranslatable in that language. The paper argues that AIDS is translatable in Ibibio. It proposes “Idiok udoño anana nsuuk,” i.e., a pandemic that defies a cure and “Udoño éd”, i.e., AIDS disease, as alternatives. It concludes that “Udoño itiaita” is misleading because it was based on a wrong assumption and has failed to portray AIDS as a killer disease to the target audience.